An oleaginous yeast platform for renewable 1-butanol synthesis based on a heterologous CoA-dependent pathway and an endogenous pathway - Yu, Aiqun (Microb Cell Fact, 2018)
BACKGROUND: Microbial biofuel production provides a promising sustainable alternative to fossil fuels. 1-Butanol is recognized as an advanced biofuel and is gaining attention as an ideal green replacement for gasoline. In this proof-of-principle study, the oleaginous yeast Yarrowia lipolytica was first engineered with a heterologous CoA-dependent pathway and an endogenous pathway, respectively. RESULTS: The co-overexpression of two heterologous genes ETR1 and EutE resulted in the production of 1-butanol at a concentration of 65 μg/L. Through the overexpression of multiple 1-butanol pathway genes, the titer was increased to 92 μg/L. Cofactor engineering through endogenous overexpression of a glyceraldehyde-3-phosphate dehydrogenase and a malate dehydrogenase further led to titer improvements to 121 μg/L and 110 μg/L, respectively. In addition, the presence of an endogenous 1-butanol production pathway and a gene involved in the regulation of 1-butanol production was successfully identified in Y. lipolytica. The highest titer of 123.0 mg/L was obtained through this endogenous route by combining a pathway gene overexpression strategy. CONCLUSIONS: This study represents the first report on 1-butanol biosynthesis in Y. lipolytica. The results obtained in this work lay the foundation for future engineering of the pathways to optimize 1-butanol production in Y. lipolytica. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-018-1014-8) contains supplementary material, which is available to authorized users.